New records of Philometra spp. (Nematoda: Philometridae) from marine perciform fishes off Florida, USA, including descriptions of two new species - Moravec, František; Bakenhaster, Micah D; Switzer, Theodore S (Folia parasitologica, 2020)
Recent examinations of marine perciform fishes from off the Florida coast in the Gulf of Mexico and Straits of Florida, USA, revealed the presence of the following six species of Philometra Costa, 1845 (Nematoda: Philometridae): P. haemulontis sp. n. (males and females) from the ovary of Haemulon plumierii (Lacepède) (type host) and H. aurolineatum Cuvier (both Haemulidae); Philometra synagridis Moravec, Bakenhaster et Fajer-Ávila, 2014 (males and females) from the ovary and testes of Lutjanus synagris (Linnaeus) (Lutjanidae); P. margolisi Moravec, Vidal-Martínez et Aguirre-Macedo, 1995 (male) from the ovary of Hyporthodus nigritus (Holbrook) (Serranidae) (new host record; probably a paradefinitive host); P. andersoni sp. n. (male) from the ovary of H. nigritus; Philometra sp. 1 (male) from the ovary of Rhomboplites aurorubens (Cuvier) (Lutjanidae); and Philometra sp. 2 (females) from the subcutaneous tissue of the anterior-most head sinuses of Hyporthodus niveatus (Valenciennes) (Serranidae). Specimens of species are described and illustrated based on light and (except for Philometra sp. 1) scanning electron microscopical examinations. Philometra haemulontis sp. n. differs from all congeners in the unique structure of the gubernaculum, whereas P. andersoni sp. n. can be differentiated from other gonad-infecting congeners parasitising the Serranidae by a combination of morphological features. Females of P. synagridis are described for the first time. Gravid females of Philometra sp. 2 are similar to those of P. morii Moravec, Bakenhaster et Fajer-Ávila, 2010, a subcutaneous parasite of Epinephelus morio (Valenciennes) (Serranidae) in the Gulf of Mexico.
Keywords: Animals; ovarium; Female; Prevalence; ženské pohlaví; Testis; Perciformes; nemoci ryb; infekce hlísticemi řádu Spirurida; Fish Diseases; Dracunculoidea; testis; Florida; prevalence; Male; interakce hostitele a patogenu; Spirurida Infections; zvířata; mužské pohlaví; Host-Pathogen Interactions; Ovary